Entry barriers to motivate multinational joint ventures: A mixed oligopoly analysis - Ali Dadpay; Hilal Yilmaz; Jane Xie; Camelia Rotaru (Asian Development Bank Institute (ADBI), 2019)
Several developing countries impose high tariffs, directly or indirectly, on imports of manufactured goods such as vehicles and machinery. In many cases governments argue that they need such policies to protect domestic manufacturing industries from foreign competition while simultaneously allowing joint ventures between domestic manufacturers and foreign ones. This study asks whether foreign businesses actually benefit more from entering a market through joint ventures where their competitors cannot enter due to high trade barriers and domestic manufacturers' monopoly. Our results answer this question in the affirmative under several scenarios. Results show that while governments use tariffs to interact strategically with other governments and foreign firms, they also use them to manage the co-integration of markets.
Keywords: L13; L23; F13; 330; international trade; mixed oligopoly market; market entry; auto industry